2019
DOI: 10.4314/jasem.v22i11.7
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance and Plasmid Profiles of Bacteria Isolated from Abattoir Effluents around Ikpoba River in Benin City, Nigeria

Abstract: Abattoirs are known all over the world to pollute the environment either directly or indirectly from their various processes. The aim of this work is to determine the bacterial load, antibiotic resistance and plasmid profile of resistant bacteria isolated from government and private abattoirs around in Ikpoba River in Benin City. Bacteria and coliform count were done using pour plating method. The total viable bacteria counts ranged 4.2x10 5 ±1.8-1.5xl0 6 ± 0.7 cfu/ml and 1.3x10 6 ± 0.1-3.1 x 10 6 ± 0.5cfu/ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 5 publications
5
6
0
Order By: Relevance
“…Similar result for chromium was reported by [41]. The values obtained for mercury and cadmium in this study was lower than the values recorded by [42], where mercury level (0.549 mg/kg) was recorded for fresh Clarias gariepinus, with a mercury concentration as high as 1.733 mg/kg recorded for dried C. gariepinus. According to the same author, cadmium level (0.52 mg/kg) was also recorded.…”
Section: Discussionsupporting
confidence: 82%
“…Similar result for chromium was reported by [41]. The values obtained for mercury and cadmium in this study was lower than the values recorded by [42], where mercury level (0.549 mg/kg) was recorded for fresh Clarias gariepinus, with a mercury concentration as high as 1.733 mg/kg recorded for dried C. gariepinus. According to the same author, cadmium level (0.52 mg/kg) was also recorded.…”
Section: Discussionsupporting
confidence: 82%
“…The higher resistance of E. coli recorded in this research is worrying as recent literature showed that many of the antimicrobial-resistant strains of E. coli that cause human urinary tract and bloodstream infections appear to have arisen from contaminated meat products (Egwuenu et al, 2018). The finding of this research is in line with the report of Atuanya et al (2018) and Savin et al (2020), who reported the resistance of E. coli isolated from slaughterhouse Effluents to Septrin and Augmentin.…”
Section: (100)supporting
confidence: 83%
“…Abattoir wastes have the ability to contaminate both surface and groundwater. Discharge from abattoir effluent contaminates the environment by introducing pathogens that can affect land and water qualities, thus endangering human, animal, and aquatic ecosystem's health and constituting a menace to human health and environmental safety [ 13 ]. The possibility of pathogens from abattoir effluent and animal waste reaching or discharging into water bodies and developing resistance to antibiotics in human infection is a concern.…”
Section: Introductionmentioning
confidence: 99%